2022
DOI: 10.1136/bmjopen-2021-053339
|View full text |Cite
|
Sign up to set email alerts
|

Effect of surgical treatment for anorectal melanoma: a propensity score-matched analysis of the Surveillance, Epidemiology, and End Results programme data

Abstract: ObjectiveAnorectal melanoma (AM) is a rare but aggressive tumour with limited information in the existing literature. This study aimed to assess the effect of surgical treatment for AM and predict the prognosis of affected patients.DesignA retrospective cohort study.SettingData of patients diagnosed with AM between 1975 and 2016 in the USA were collected from the Surveillance, Epidemiology, and End Results (SEER) database.ParticipantsThis study enrolled a total of 795 patients with AM from the SEER database an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…The authors observed that despite the slightly better 5-year survival rate of LE (32% vs 23%), a statistically significant reduction in recurrence was found in APR group (OR=0.15; 95% CI: 0.08-0.28, p<0.00001) 9 . Lei et al 11 analyzed 795 ARM patients from the USA Surveillance, Epidemiology, and End Results (SEER) database. A nomogram based on a multivariate Cox regression model was generated to predict ARM-Specific Survival.…”
Section: Discussionmentioning
confidence: 99%
“…The authors observed that despite the slightly better 5-year survival rate of LE (32% vs 23%), a statistically significant reduction in recurrence was found in APR group (OR=0.15; 95% CI: 0.08-0.28, p<0.00001) 9 . Lei et al 11 analyzed 795 ARM patients from the USA Surveillance, Epidemiology, and End Results (SEER) database. A nomogram based on a multivariate Cox regression model was generated to predict ARM-Specific Survival.…”
Section: Discussionmentioning
confidence: 99%
“…ER refers to tumour resection and LN removal, and LR refers to tumour resection without LN dissection. Two studies based on the SEER database showed that compared with LR, ER did not increase the survival rate of patients with primary melanoma of the AM,24 25 even with confounding variables controlled 25. However, patients having regional metastasis with LN density less than 20% may gain benefits with ER.…”
Section: Discussionmentioning
confidence: 99%
“…22,23 Furthermore, several retrospective studies demonstrate no survival benefit for APR compared to LE, (Tables 2 and 3). 2,[4][5][6][7][8][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] Thus, in the absence of any demonstrable survival benefit, APR is now discouraged for the treatment of anorectal melanoma whenever technically feasible.…”
Section: Primary Tumor Resectionmentioning
confidence: 99%
“…Prognosis of early cutaneous melanoma is relatively favorable with 5‐year survival rates of 99.5%, 70.6%, and 31.9% for localized, regional, and distant cutaneous melanoma, respectively 1 . Anorectal melanoma is a rare subtype of melanoma and accounts for only 1% of all melanoma diagnoses and 25% of mucosal melanomas in the United States; however, its incidence is increasing 2–5 . Despite the excellent general prognosis for localized cutaneous melanoma and recent improvements seen in survival for patients with distant metastatic disease, the outcomes for most patients with anorectal melanoma remain poor.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation